Miłosza pobyty w równoległych (przekładowych) światach - Rajewska, Ewa (My University, 2012)
The well known interpretation of Miłosz’s work as an attempt to capture fulness, has been most fully formulated by Jan Błoński’s “Miłosz jak świat” [“Miłosz like a World”]. The author of the article provides a more detailed version of the interpretation, presenting Miłosz’s work as a multiplied universe: in translation and in self-translation. Miłosz’s universe has been multiplied through translation: undertaking translation of so many and so various poets, Miłosz, by extension, translated their poetic worlds. In doing so, he had to go beyond the borders of the world of his own idiom and imagination. Miłosz’s attempts at transgression beyond the borders of his own language and imagination, and into a poetic “parallel universe”, are conducted, according to the present author, in two ways: through similarity and through completion. Miłosz translates works which he which he selected on the principle of an exceptional poetic kinship (for example in his Excerpts from Useful Books). Other translations were an opportunity to test himself on an intriguing poetic material, which he himself would not be willing to create (for example in poetry by Anna Świrszczyńska).
Miłosz’s Sojourns in Parallel (Translation) Universes
Keywords: Czesław Miłosz; Anna Świrszczyńska; translation; authorial poetics; poetics of translation